Prairie Interlace Weaving, Modernisms, and the Expanded Frame, 1960-2000 - Hardy, Michele; Long, Timothy; Krueger, Julia (Art in Profile, 2023)
Innovative textile-based artwork exploded across the Canadian Prairies in the second half of the twentieth century. Melding craft traditions with modern and modernist movements in art and theory, a diverse body of creators opened a beautiful new chapter in textile art. Prairie Interlace brings together some of the most important scholars of art and craft in Canada to examine the work of forty-eight artists working with textiles from the 1960s to 2000. Recapturing and recording lost histories, this book explores both artists working with textiles and centres of textile study and production, paying special attention to the contexts in which artworks were produced. Indigenous scholars, experts in textile techniques, and experts in Prairie textile history provide fascinating insight into an artistic movement which, until now, has been largely overlooked. Featuring over one hundred and fifty beautiful full-colour images of textile works, many of which have never before been photographed for print, Prairie Interlace provides an opportunity to discover a fascinating movement which has not received the attention it deserves and invites further investigation of this rich period in Canadian art history. Developed from the travelling exhibition of the same name, Prairie Interlace is a collaboration between Nickle Galleries, University of Calgary in Calgary, AB and the MacKenzie Art Gallery, Regina, SK.